Analisis Maqāṣid al-Syarī‘ah terhadap Praktik Tinggal Satu Atap Pascaperceraian - Adinda Amalia Harahap; Zainal Arifin Purba (CV Global Research Publication, 2026)
This study aims to examine the law of living under one roof after divorce from the perspective of maqāṣid al-syarī’ah. This phenomenon often occurs in society due to economic factors and the interests of children. The study used a qualitative method with an empirical normative approach through interviews and literature studies. The results of the study indicate that living under one roof after divorce can have various legal and social implications, especially related to the boundaries of interaction between ex-husband and wife. Despite being divorced, the couple continues to live in the same house with the main goal of protecting the child's psychological condition so that they do not feel the negative impact of their parents' divorce. The relationship between the two is no longer based on an emotional bond as a couple, but rather is limited to carrying out their roles and responsibilities as parents. This condition indicates that the decision to continue living together is a form of parental effort to protect the child's mental well-being, even though their marriage has substantially ended. From the perspective of maqāṣid al-syarī’ah, the law of living under one roof after divorce is reviewed based on the objectives of sharia in protecting offspring (ḥifẓ al-nasl) and honor (ḥifẓ al-‘irḍ). This study concludes that living under one roof after a divorce is essentially permissible if there is an urgent need and greater good, such as child protection and economic constraints, while still maintaining sharia boundaries to prevent harm and violations of religious norms.